Atomic-scale cation dynamics in a monolayer VOX/α-Fe2O3 catalyst. Issue 126 (10th December 2015) - Feng, Z.; Ma, Q.; Lu, J.; Feng, H.; Elam, J. W.; Stair, P. C.; Bedzyk, M. J.
Abstract : A combination of in situ XAS and FTIR shows the redox-induced vanadium cation dynamics on the surfaces of Fe2 O3 powders. Abstract : Catalytic reactions are associated with dynamical changes in the catalyst that include the oxidation state and local structural variations. The understanding of such dynamics, particularly at the atomic-scale, is of great importance for revealing the activity and selectivity of the catalyst in numerous reactions. Combining in situ X-ray absorption spectroscopy with in situ diffuse reflectance infrared Fourier transform spectroscopy, we studied the redox-induced dynamical changes for a VO X monolayer catalyst supported on a α-Fe2 O3 powder. The results show that several co-existing VO X species reversibly change their V oxidation states between +5 and +4, in concurrence with a structural change from two-dimensional chains to well connected V–O–V networks. These changes are also associated with the breaking and formation of the VO vanadyl group. This combined study provides new insight into how VO X species change during catalytic reactions, which leads to proposed atomic-scale models for the redox-induced dynamics of the catalyst.